1999
DOI: 10.1063/1.478758
|View full text |Cite
|
Sign up to set email alerts
|

Fluorobenzene⋯water and difluorobenzene⋯water systems: An ab initio investigation

Abstract: Recently, Brutschy and co-workers have reported the spectra of (substituted benzene)⋯(H2O)n systems. To investigate the possibility of these systems exhibiting a π–H kind of bonding interaction as observed in benzene⋯(H2O)n systems, we have carried out extensive ab initio calculations on different conformations of the fluorobenzene⋯(H2O) and p-difluorobenzene⋯(H2O) systems using various basis sets. Our results indicate that unlike the π interaction observed in benzene⋯(H2O)n, the O–H of the water molecule is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
125
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 106 publications
9
125
1
Order By: Relevance
“…A strong linear correlation between the value of the electrostatic Figure 9. a) Global minimum C 6 H 5 F···H 2 O complex, featuring H···F and CH···O interactions, rather than OH/p interactions, as reported by Brutschy et al [60] b) Low-lying conformer of reported by Neusser and coworkers. [61] potential minimum and the cation/p binding energy was found.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…A strong linear correlation between the value of the electrostatic Figure 9. a) Global minimum C 6 H 5 F···H 2 O complex, featuring H···F and CH···O interactions, rather than OH/p interactions, as reported by Brutschy et al [60] b) Low-lying conformer of reported by Neusser and coworkers. [61] potential minimum and the cation/p binding energy was found.…”
mentioning
confidence: 61%
“…The effect of aryl fluorine substitution on OH/p interactions have also been discussed. [60,62] For example, Brutschy et al showed [60] that the global minimum complexes of water with fluorobenzene and p-difluorobenzene do not actually exhibit an OH/p interaction, but instead feature a cyclic arrangement of OH···F and CH···O interactions (see Figure 9 a). For the C 6 F 6 -H 2 O complex, the global minimum structure also does not exhibit an OH/p interaction, but instead has both H atoms pointing away from the ring (i.e.…”
Section: Oh/p Interactionsmentioning
confidence: 97%
“…The fluorobenzene molecule has received considerable attention from quite different fields of research, ranging from its interest in cation-p interactions in biological molecules [1], as environmentally relevant species among other aromatic molecules [2], or in the study of van der Waals systems, formed by aromatic molecules linked to a rare gas atom [3][4][5] or to other species like methanol, N 2 or water [6][7][8]. On the other hand, the vibrotational spectroscopy of this molecule has been scarcely studied, mainly because the large moment of inertia of the molecule induces a crowded rovibrational spectrum, and makes the analysis complicated.…”
Section: Introductionmentioning
confidence: 99%
“…7 This is consistent with earlier calculations. 8,9 The remaining H atom appears to lie out of the plane. This change in the nature of the aromatic-water interaction has led us to explore the complexes of water with the series of difluorobenzenes ͑DFBs͒, viz.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies of the pDFB-H 2 O complex have been reported, [7][8][9]14,15 however, studies of the ortho and meta isomers appear restricted to a Ph.D thesis. 10 The S 1 ← S 0 transition of the pDFB-H 2 O complex has been studied using both one and two-color 1 + 1 REMPI.…”
Section: Introductionmentioning
confidence: 99%